Indigenisation and history: how opera in South Africa became South African opera - Roos, Hilde (Acta Academica: Critical views on society, culture and politics, 2012)
In South Africa, the exposure of opera to local cultures and circumstances has in time resulted in a number of opera productions that have departed from Western aesthetic norms and prompted innovations to the genre. These innovations can be traced in newly created operas as well as in the production of a number of operas from the standard canon that have been ‘translated’ to local contexts and social realities. This article explores the historical trajectory of opera production in South Africa from 1801 to the present through the lens of indigenisation and shows that, in its most subtle form, this phenomenon can be traced in local opera productions long before the issue of the reflection of indigenous cultures in opera became relevant. In constructing this history, the author hopes to identify moments when one musical element became another, or changed sufficiently to become a similar, but different element. Clearly, in discovering the South African roots of opera and understanding the many projects that currently characterise the opera scene in this country, the issue is not only one for cultural or textual analysis, but also, very pertinently, a matter for historiography.